Drawing lifelike portraits with Lee Hammond - Hammond, Lee; North Light Media; Artistsnetwork.tv productions ([United Kingdom] : North Light Media, 2009)
Lee Hammond demonstrates how to achieve lifelike portraits through smooth blending and gradual tonal changes. She shows you how to create subtle gradation changes, and shading of a sphere for more realism in your drawings
Instructor: Lee Hammond
DVD format
Keywords: Portrait drawing -- Technique